Peranan perpustakaan dalam pencegahan plagiarisme: Tinjauan literatur naratif - Yusmafida, Raisya Rizka Nayla; Amar, Siti Chaerani Djen; Rukmana, Evi Nursanti (Faculty of Communication, Padjadjaran University, 2024)
This study examines the vital role of libraries in preventing plagiarism, a prevalent phenomenon in academic and professional spheres. The primary objectives are to evaluate libraries' contributions to plagiarism prevention, optimize the use of information resources to mitigate such practices and analyze the impact of plagiarism on users and information institutions. The methodology employed is a narrative literature review, analyzing eleven references related to libraries' role in plagiarism prevention. Findings indicate that libraries play a significant role through comprehensive information resource provision and services. Utilization of information sources is achieved through effective collection management and implementation of technology in service processes. The study identifies negative impacts of plagiarism, including career obstacles and future opportunities for perpetrators, as well as detriment to original information owners. For libraries, plagiarism can diminish institutional credibility and integrity. In conclusion, libraries have a crucial role in preventing plagiarism, emphasizing the importance of awareness and proactive measures in combating this practice. This research underscores the necessity for libraries to remain vigilant and actively engage in plagiarism prevention, thereby maintaining academic integrity and supporting ethical information use in both educational and professional environments.